please answer my question
Attachments:
![](https://hi-static.z-dn.net/files/d61/6bf611c91e3e818ae7777f0b86210d89.jpg)
Answers
Answered by
1
Answer:
let's take denominator first
√10+ √20+ √40- √5- √80
=√10+ 2√5+ 2√10- √5-4√5
=3√10- 3√5
=3(√10-√5)
now divide numerator by denominator
we get 5(√10-√5)
=5(√10+15)÷5
=√10+√5
sushmita2005:
sorry but steps
Similar questions
Math,
7 months ago
Political Science,
7 months ago
Math,
1 year ago
Science,
1 year ago
Social Sciences,
1 year ago
Business Studies,
1 year ago